ARUNG: A Cultural Heritage-Based Application for Android Augmented Reality in Learning Geometry - Munir, Nilam Permatasari; Anas, Aswar; Musa, Lisa Aditya Dwiwansyah; Ndemo, Zakaria (Yayasan Keluarga Guru Mandiri, 2026)
Although Augmented Reality (AR) has been extensively discussed and reported in mathematics education, there is limited research on its integration with local culture. This study introduces ARUNG, an Android-based application that integrates cultural heritage into geometry education. The innovation focuses on three main aspects: the integration of local cultural heritage into ARUNG, the design of the ARUNG system for geometry learning, and the analysis of the effectiveness on geometry concept comprehension. A research and development (RD) study was conducted, involving three stages: input, output, and feedback. ARUNG was applied to 25 junior high schools in the eighth grade. Data on the conceptual understanding test results were analyzed to test the research hypothesis using a paired t-test. Cultural heritage markers integrated into ARUNG included Walasuji (cube), the walls of the Jami Tua Mosque in Palopo (rectangular prism), the Soko Guru pole (twelve-sided prism), the royal tomb of Lokko’e (square prism), and the PNIEL church (octagonal pyramid). The findings revealed that students' average comprehension of geometry concepts improved after using ARUNG compared to before. This research contributes to the field by introducing an innovative AR learning medium that incorporates cultural heritage, thereby promoting cultural awareness.